Zr/Mg, Zr/Sr and Zr/Zn co-doped hydroxyapatites: Synthesis and characterization - Kaygili, Omer; Keser, Serhat (Elsevier Sci Ltd, 2016)
Zr/Mg, Zr/Sr and Zr/Zn co-doped hydroxyapatite samples, having high crystallinity, prepared by sol-gel synthesis were characterized via X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. Based on the XRD results, it is shown that the kind of co-additives significantly affect both lattice parameters, as well as the crystallite size. According to the SEM images, it is observed that all the samples are composed of fine-grained particles with different shapes and dimensions. EDX analysis revealed that there is no impurity for all the as-synthesized samples, the molar ratios of (Ca+Zr+Mg)/P, (Ca+Zr+Sr)/P and (Ca+Zr+Zn)/P are found to be 1.68, 1.65 and 1.69, respectively and these molar ratios almost equal to the stoichiometric value of 1.67. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electron microscopy; X-ray methods; Apatite; Sol-gel process